Increased incidence of Pythium stem rot in cowpea treated with benomyl and related fungicides - Williams, R.J.; Ayanaba, A. (Scientific Societies, 1975)
In six replicated field trials during a 3-year period the incidence of cowpea wet stem rot caused by Pythium aphanidermatum was significantly greater in plots treated with benzimidazole (BZ) fungicides than in plots treated with non-BZ fungicides and nontreated plots. In laboratory studies, the growth of P. aphanidermatum in corn-meal agar was unaffected by the addition of up to 250 µg/ml active ingredient of the BZ fungicides. It seems likely that the broad-spectrum, yet selective, BZ fungicides favor the activity of P. aphanidermatum by suppressing antagonists and competitors.